2021
DOI: 10.3390/jmse9111254
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Mineral Properties of Quaternary Deep-Sea Sediments in the Central-Tropical Pacific and Its Response to the Mid-Pleistocene Transition

Abstract: Global climate and oceanic water masses have undergone profound changes during the middle Pleistocene transition; however, due to a lack of foraminiferal fossils, the nonfossiliferous pelagic deposits were less detected in previous reports. In this work, a gravity core from the Kamehameha Basin in the Central Pacific was studied in terms of magnetostratigraphy, clay mineral and geochemical elements. The main results are: (1) nine magnetozones are recognized in the core, which can be correlated to the geomagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…The REY content of the sediments is mainly related to the quantity of fish teeth [6,8,[62][63][64] and micronodules [11,59,60], which are intermediate carriers of REY in the early stage of sedimentation, and the REY will migrate from the micronodules to the fish teeth during diagenesis. Asian dust (black dotted line) after [53][54][55][56][57][58]; Marcus-Wake Seamounts sediment (light blue, green, yellow and red lines) after [6,16,17]; micronodules (blue line), bioapatite fossils (purple line) and philipsites (brown line) after [6]; basalt (pink line) after [65]; bottom water (light blue dotted line) after [36], and volcanic debris (red dotted line) after [66]. [44] REY pattern of all the samples in this study and some references.…”
Section: Sources and Carriers Of Reymentioning
confidence: 99%
See 4 more Smart Citations
“…The REY content of the sediments is mainly related to the quantity of fish teeth [6,8,[62][63][64] and micronodules [11,59,60], which are intermediate carriers of REY in the early stage of sedimentation, and the REY will migrate from the micronodules to the fish teeth during diagenesis. Asian dust (black dotted line) after [53][54][55][56][57][58]; Marcus-Wake Seamounts sediment (light blue, green, yellow and red lines) after [6,16,17]; micronodules (blue line), bioapatite fossils (purple line) and philipsites (brown line) after [6]; basalt (pink line) after [65]; bottom water (light blue dotted line) after [36], and volcanic debris (red dotted line) after [66]. [44] REY pattern of all the samples in this study and some references.…”
Section: Sources and Carriers Of Reymentioning
confidence: 99%
“…Bi et al also found that the REY content of sediments from core C on the southeastern side of the Niulang Guyot is significantly higher than that from core B on the other side (Figure 6b), and that there is a REY-rich layer with a REY content of more than 2000 ppm in the lower part of core C [6]. Asian dust (black dotted line) after [53][54][55][56][57][58]; Marcus-Wake Seamounts sediment (light blue, green, yellow and red lines) after [6,16,17]; micronodules (blue line), bioapatite fossils (purple line) and philipsites (brown line) after [6]; basalt (pink line) after [65]; bottom water (light blue dotted line) after [36], and volcanic debris (red dotted line) after [66]. [53][54][55][56][57][58]; highly REY-rich mud (red solid circle) after [6,16,17]; basalt (pink square) after [65]; micronodules (blue diamond), bioapatite fossils (red cross) and philipsites (orange triangle) after [6], and volcanic debris (orange pentagram) after [66].…”
Section: Effect Of Seamounts On Rey Enrichmentmentioning
confidence: 99%
See 3 more Smart Citations